Transformations of Byron in the literature of British India - Ni Fhlathuin, Maire (Cambridge University Press, 2014)
This essay examines the reception of Byron’s work, and some responses to it, among the poets of the British community in India during the first half of the nineteenth century. The first section sketches some of the routes by which Byron’s work and accounts of his life were circulated and read in India and demonstrates the impact of his work on the poets of British India. These poets co-opted Byronic texts into their own writings in the form of epigraphs and other citations and allusions, composed responses to Byron and his work, and imitated the tropes, formats and themes of Byron’s poetry. The second section of the essay looks in more detail at selected examples of the many adaptations and imitations of Byron’s work that proliferated during this period. In these poems, Byronic models are propriated by writers whose chosen professions or relationships have the effect of aligning them with the colonial project of the East India Company. They re-imagined the encounter with the romanticized Orient that characterizes many of Byron’s works in response to the specific political and cultural contexts of British India in the nineteenth century.